Human rights and science: Leopoldina Symposium ; Berlin, October 6 to 7, 2010 - Eckert, Johannes; Zenner, Hans-Peter (Nova acta Leopoldina, 2011)
Human rights include the right to development, a clean and healthy environment, and peace. For scientists and their institutions, freedom to teach and carry out research is an especially precious commodity. This volume reports on a symposium organized by the Human Rights Committee (HRC) of the German National Academy of Sciences Leopoldina that was dedicated to the subject of human rights and science. It brought together representatives from academies and universities of 12 European countries. The articles demonstrate the significance of human rights in legislation, day-to-day business operations, research on humans, international scientific partnerships and development aid. A reorientation of research is necessary in order to take the needs of threatened and marginalized peoples into consideration. The articles report on human rights situation in various countries and the international activities coordinated by the International Human Rights Network of Academies and Scholarly Societies (IHRN) on behalf of people in academia who have been exposed to human rights violations. All of the articles are in English.